Pathways for Social Equity: An Audit of Bureaucratic Representation, Diversity, and Cultural Competency in Florida Nursing Homes - Austin M. McCrea; Kenicia Wright; Xiaoyang Xu; Noah Pruitt (Journal of Social Equity and Public Administration)
Social equity is a central concern in public service provision. As a concept, social equity is comprised of several disparate concepts including representative bureaucracy, diversity management, and cultural competency, each focusing on a specific function necessary for achieving equitable processes, outputs, and outcomes. While many organizations implement reforms across all three of these dimensions simultaneously, existing applications in the literature tend to only focus on one at a time—potentially obfuscating the true impact of social equity reforms within public organizations. By constructing a dataset of over 600 nursing homes in Florida, our descriptive analysis reveals that nursing homes are unrepresentative, lack diversity, and tend to provide culturally competent care in underperforming homes. We further examine the sectoral differences between for-profit homes and not-for-profit. Our article contributes to the literature by providing an in-depth audit of how nursing homes practice representation, diversity, and cultural competency.